2018
DOI: 10.1017/wsc.2018.70
|View full text |Cite
|
Sign up to set email alerts
|

Target-Site Resistance Mechanisms to Tribenuron-methyl and Cross-resistance Patterns to ALS-inhibiting Herbicides of Catchweed Bedstraw (Galium aparine) with Different ALS Mutations

Abstract: Catchweed bedstraw (Galium aparine L.) is a problematic dicot weed that occurs in major winter wheat (Triticum aestivum L.) fields in China. Tribenuron-methyl has been widely used to control broadleaf weeds since 1988 in China. However, overuse has led to the resistance evolution of G. aparine to tribenuron-methyl. In this study, 20 G. aparine populations collected from Shandong and Henan provinces were used to determine tribenuron-methyl resistance and target-site resistance mechanisms. In dose–response exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In these populations, the NTSR mechanism may be dominant, and further research is needed. The Trp-574-Leu mutation was mainly responsible for penoxsulam resistance in E. crus-galli, and the same substitution has been documented in other ALS inhibitor-resistant weeds, including catchweed bedstraw (Galium aparine L.) (Deng et al 2019b) . The variation in ALS copy number was also observed in shortawn foxtail (Alopecurus aequalis Sobol.)…”
Section: Cloning and Sequence Analysis Of Als And Accase Genesmentioning
confidence: 64%
“…In these populations, the NTSR mechanism may be dominant, and further research is needed. The Trp-574-Leu mutation was mainly responsible for penoxsulam resistance in E. crus-galli, and the same substitution has been documented in other ALS inhibitor-resistant weeds, including catchweed bedstraw (Galium aparine L.) (Deng et al 2019b) . The variation in ALS copy number was also observed in shortawn foxtail (Alopecurus aequalis Sobol.)…”
Section: Cloning and Sequence Analysis Of Als And Accase Genesmentioning
confidence: 64%
“…This study found two amino acid substitutions (Trp‐574‐Leu or Gly‐654‐Tyr) in ALS in the imazethapyr resistant A. retroflexus population. The Trp‐574‐Leu substitution has previously been documented as providing ALS‐inhibiting herbicide resistance in many resistant weed species including cocklebur ( Xanthium strumarium ), 22 A. retroflexus , 18 flixweed ( Descurainia sophia L.), 23 and bedstraw ( Galium aparine ) 24 . However, there has not been any report on the Gly‐654‐Tyr substitution endowing ALS resistance in plant species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Pro-197-Ser mutation in D. sophia exhibited cross-resistance to SU and TP herbicides and showed no cross-resistance to PTB and IMI herbicides (Deng et al 2014). The same mutation displayed resistance to SU, TP, and PTB herbicides in M. aquaticum (Liu et al 2013) and broad-spectrum resistance to SU, TP, PTB, and IMI herbicides in E. prostrata (Li et al 2017) and G. aparine (Deng et al 2019). Therefore, it is necessary to determine the specific cross-resistance patterns for the newly identified herbicide-resistant biotype.…”
Section: Cross-resistance To Other Als-inhibiting Herbicidesmentioning
confidence: 99%